Placing Culture into the “Lifeless” Business World - Alexey Spirin (Journal of Economic Sociology, 2015)
Lyn Spillman’s new book Solidarity in Strategy: Making Business Meaningful in American Trade Associations considers the historical development and evolution of American business associations and their role in the contemporary economic system as a special organizational form of interactions among business actors. In the broadest sense, Spillman argues that associations are “cultural producers for economic action” [Spillman: 79]. Moreover, the author pays attention to the association’s ability to survive under complex economic and political conditions. Spillman analyzes the processes through which associations have transformed from unstable, redundant and limited “dinner clubs” to powerful and authoritative structures, wielding practical tools for solving complex market objectives.The book review addresses the issue of theoretical background of the book, and more precisely this review focuses on Lyn Spillman’s synthesis of Weber’s conception of self interest with Durkheim’s view of collective action. In terms of this framework Lyn Spillman argues against a conventional statement that associations are solely a conspiracy of manufacturers who narrowly target to act against consumer. In contrast, business actors are seen to be altruistic, focusing on the collective good and group identification rather than egoistic or placing profit center stage. All in all, the aim of this book review is to represent Spillman’s key ideas, analyze the author’s logic and finally endeavor to grasp how and to whom this book could be beneficial and where it might be implemented.